Parotocinclus yaka, a new species of armored catfish (Loricariidae: Hypoptopomatinae), from the Amazon basin in Brazil - Lehmann A., Pablo; Lima, Flávio C. T.; Reis, Roberto E. (Zootaxa, 2018)
Parotocinclus yaka is described as a new species of hypoptopomatine cascudinho from tributaries of the Rio Tiquié, tributary to the Rio Uaupés, upper Rio Negro drainage, Amazon basin, Amazonas State, Brazil. The new species is distinguished from its congeners in northeastern and southeastern Brazil by having the cheek canal plate elongated posteriorly on the ventral surface of the head and in contact with the cleithrum. Parotocinclus yaka is diagnosed from the Parotocinclus species of the Amazon, Orinoco and Guianas watersheds by having a conspicuous dark spots smaller than the pupil diameter distributed dorsally and laterally on the head; it is also differentiated from P. polyochrus (Casiquiare, Venezuela), P. longirostris (Rio Amazonas, Brazil), and P. eppleyi (Río Orinoco) by the absence of a Y-shaped light mark dorsally on the head. In addition, the absence of premaxillary and dentary accessory teeth and the presence of a Y-shaped spot on the snout distinguish the new species from P. collinsae (Essequibo River, Guyana), P. halbothi (Rio Trombetas, Brazil and Marowijne River, Suriname) and P. variola (Río Amazonas, Colombia). Parotocinclus yaka also differs from P. amazonensis (lower Amazon basin), P. aripuanensis (lower Amazon basin), P. britskii (Guyana, Suriname, eastern Venezuela, and Amapá State, Brazil), and P. dani (Rio Tapajós basin), by having more numerous oral teeth. The new species described herein is part of the group of small cascudinhos usually associated with marginal or submerged vegetation and submerged logs, of moderate current and clear transparency, found in conserved habitats in streams of the Amazon, Orinoco and Guianas rivers.